PENERAPAN MANAJEMEN WAKTU MENGGUNAKAN NETWORK PLANNING (CPM) PADA PROYEK KONSTRUKSI JALAN (STUDI KASUS PENINGKATAN JALAN Sp. BEREMBANG – Sp. JAMBI KECIL) - Elvira Handayani; Dedy Iskandar (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
One of the methods in the application of Network Planning on construction projects is the Critical Path Method (CPM).Use of critical path method is to be able to know the the critical path of a project in which an activity can not be delayed, so that the execution time can be controlled to determine the earliest and the latest of starting time. As such factors can delay the project in minimizingRoad Improvement Works Sp. Berembang - Sp. Small Jambi has a contract value of Rp. 9,969,162,000.00 and the turnaround time is 217 calendar days. Application of CPM on the job resulted in an accelerated completion of work to 210 calendar days and 6 work items that are on the critical path. Acceleration time of completion of the work provides implementation costs Rp. 9,956,247,162.00 or additional profit of Rp. 12,914,838.00.Keyword:  Time management, Critical path method, road construction